+0

# trig

0
68
2

csc(acos(u))

Guest May 25, 2017
Sort:

#1
+4168
+3

$$\csc(\arccos u ) \\~\\ =\frac{1}{\sin(\arccos u)} \\~\\ =\sqrt{ (\frac{1}{\sin(\arccos u)})^2 } \\~\\ =\sqrt{ \frac{1}{\sin^2(\arccos u)} } \\~\\$$

And... sin2θ = 1 - cos2θ

$$=\sqrt{ \frac{1}{1-\cos^2(\arccos u)} } \\~\\ =\sqrt{ \frac{1}{1-\cos(\arccos u)\cos(\arccos u)} } \\~\\ =\sqrt{ \frac{1}{1-uu} } \\~\\ =\frac{1}{\sqrt{1-u^2}} \\~\\$$

hectictar  May 25, 2017
#2
+89810
+2

This is how I would do it.

let acos(u) = alpha

Draw a right angled triangle and let alpha be an acute angle.

since  cos( alpha) = u/1

let  the adjacent side by u and the hypotenuse be 1

using pythagoras's theorem you get

$$\text{opposite side=}\sqrt{1-u^2}$$

$$cosec(\alpha)=\frac{hyp}{adj}=\frac{1}{\sqrt{1-u^2}}$$

but you do not know which quadrant alpha is in so

$$cosec(\alpha)=\pm\frac{1}{\sqrt{1-u^2}}$$

Melody  May 25, 2017

### 8 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details